The Effect of Motivation, Stress and Work Environment on the Performance of Tax Audit in KPP Madya Makassar - Rabiyah, Ulfa (Phinisi Applied Accounting Journal, 2023)
To produce a quality tax audit, of course, begins with the good performance of the tax examiner. The results of the evaluation of the inspection activities of the Makassar Madya Tax Service Office for the period 2018 to July 2021 show that SP2 is still high at Makassar Madya KKP every year. If it is related to the performance of the tax auditor, it means that the tax audit carried out by the tax auditor must be in accordance with the purpose of the tax audit, namely to test taxpayer compliance and other purposes in order to implement the provisions of tax laws and regulations. The research method is quantitative research using questionnaires, the questionnaires are distributed to 31 tax examiners at KPP Madya Makassar. The results of the study found that motivation had a positive and insignificant effect on the performance of the tax examiner at the Makassar Intermediate Tax Service Office. Stress does not have a positive and insignificant effect on the performance of the tax examiner at the Makassar Madya Tax Service Office and the work environment has a positive and significant effect on the performance of the tax examiner at the Makassar Intermediate Tax Office. expected to examine other variables that affect the performance of tax examiners such as compensation, work culture, training, personality, career planning and employee empowerment.Keywords: Motivation, Stress, Work Environment, Performance